Dynamic response of sandwich plates with GLARE face-sheets and honeycomb core under metal foam projectile impact: Experimental and numerical investigations - Zhang, Jianxun; Zhu, Yuqing; Li, Kaikai; Yuan, Hui; Du, Jinlong; Qin, Qinghua (International journal of impact engineering, 2022)
•Dynamic response of sandwich plates with GLARE face-sheets under metal foam projectile impact is studied.•Effects of impulse and thickness on dynamic response are studied by single impact experiments.•The ability of resisting multiple impacts and the ultimate failure mode are measured.•The numerical results are in good agreement with experimental ones. Aluminum honeycomb sandwich plate with fiber metal laminate (FML) as panel can combine the advantages of FML face-sheet and honeycomb core, and has advantages of high specific strength / specific stiffness, lightweight and good energy absorption performance. In this paper, the dynamic response of aluminum honeycomb sandwich plates with Glass Laminate Aluminum Reinforced Epoxy (GLARE) face-sheets under metal foam projectile impact is studied. The single foam projectile impact test is conducted to study the dynamic response of honeycomb sandwich plates with GLARE face-sheets. The debonding between metal and composite layers of the front face-sheet, the fiber fracture, buckling, shear and fracture of core are observed. Also, the multiple foam projectile impact test is carried out to study the impact resistance of the sandwich plate. The numerical calculation is conducted, numerical results are compared with experimental ones. Influences of the impulse, face-sheet thickness, fiber laying angle, honeycomb height, wall thickness of core and cell length of honeycomb on impact resistance and energy absorption of sandwich plates are discussed. It is found that the improvement range of the maximum deflection of back face-sheet gradually decreases with the increase of face-sheet thickness. In addition, by increasing the impulse, decreasing the face-sheet thickness and decreasing the core stiffness, the energy absorption of sandwich plates under metal foam projectile impact can be enhanced. These findings can be used to guide the optimal design of FML sandwich structures under metal foam projectile impact.